Storynomics Tinggalan Arkeologi: Mediasi antara Motivasi dan Minat Berkunjung ke Candi Tebing Tegallinggah Desa Bedulu Gianyar Bali - I Wayan Sukanadi; Denok Lestari; Kadek Ayu Ekasani; Ni Made Ayu Natih Widhiarini (Jurnal Kajian Bali (Journal of Bali Studies), 2022)
For the sake of tourism recovery during the post-pandemic period, a storynomic promotion strategy is currently being developed by Indonesian government, and is considered effective in triggering the curiosity and visiting interest of tourists. This study aims to identify the role of storynomics as a moderating variable in strengthening motivation and interest to visit the Tebing Tegallinggah Temple site in Bedulu village, Gianyar, Bali. First, storytelling stories were collected through field research by interviewing selected informants, as well as randomly distributing questionnaires. Second, historical data and documentation were classified and analyzed qualitatively, while respondents' answers were assessed using Smart PLS. Third, the results of data analysis are presented through narrative descriptions supported by tables and figures for visualization. The results showed that motivation and storynomic had a less significant effect on the visiting interest of the respondents, most of whom were young. This research is expected to speed up the tourism recovery as well as to contribute to the sustainability of archaeological heritage as special interest tourist destination in Gianyar regency in particular and Indonesia in general.